Portraits of Labor Market Exclusion 2.0 : Country Policy Paper for Bulgaria - Karacsony, Sandor (World Bank, Washington, DC, 2018)
This is a joint study between the European Commission (EC), the World Bank, and the Organization for Economic Cooperation and Development (OECD), which aims to inform employment support, activation, and social inclusion policy making, through an improved understanding of labor-market barriers.